PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN TENTANG PENCEGAHAN KAMBUH ULANG GASTRITIS PADA PASIEN DI PUSKESMAS PUTRI AYU KOTA JAMBI - Arifmon Zuliandana; Tina Yuli Fatmawati (Universitas Baiturrahim, 2016)
Background:Gastritis is an inflammation of the stomach lining tissue disorder most often caused by diet. Based on data from the City Health Office of Jambi in Year 2013 in PHC gastritis ranks 4th with the number of visits of 24 213 people. Putri Ayu at the health center of gastritis in the top 10 most prevalent diseases. The aim of research to determine the effect of health education on patients' knowledge about the prevention of relapse over Putri Ayu PHC gastritis in the city of Jambi.Method:This research was conducted at the health center Putri Ayu Jambi, on 22 May 2015 s / d 30 May 2015 where health education was held on Friday 29th May 2015 with respondents as many as 20 patients. This study is a pre experimentdengan draft design one group pretest-posttest. Data obtained by filling out the questionnaire and the analysis of univariate and bivariate by using t-test.Result: of the group who have not given health education (pretest), namely the level of knowledge obtained with the results of the average (mean) = 5.8. Then given treatment in the form of health education and the level of knowledge obtained posttest with the results of the average (mean) = 8.7. Bivariate data analysis by using statistical test obtained t-test p-value = 0.000, the p-value <α (0.05). This shows the significant influence of health education on the knowledge of the respondent.Gastritis patients are advised to eat regularly on the clock the same every day, eat snacks between meals to arrive so that the stomach is not empty, eat less spicy and sour. Caution in using NSAIDs such as aspirin and paracetamol. Must be consumed after meals, rest and managing stress.Keywords : Knowledge, Health Education Prevention of relapse regastritis